2002
DOI: 10.1139/v02-008
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic dechlorination of atrazine

Abstract: Atrazine (2-chloro-4-ethylamino-6-isopropylamino-s-triazine), a photosynthetic inhibitor that is used in large quantities for weed control in corn and sorghum, is dechlorinated in aqueous solution upon electrolysis at a reticulated vitreous carbon cathode in the presence of noble-metal catalysts. Electrocatalytic hydrogenolysis to 2-ethylamino-4-isopropylamino-s-triazine occurs in quantitative yield, and is most efficient with palladium-based catalysts. Current efficiency increases with atrazine and catalyst c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The use of ECH for the dechlorination of chloroaromatic compounds is potentially advantageous compared with traditional techniques such as adsorption on activated carbon or incineration. Recent studies have shown that the dechlorination of 4-CP (4-chlorophenol) by electrocatalytic hydrogenation on a palladized carbon cloth and of chlorophenoxy acetic acids on palladium-loaded carbon felt can be performed with good efficiencies. According to the literature, , the mechanism of the electrocatalytic hydrogenolysis of a carbon−halogen bond involves the steps described in eqs 1−4 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ECH for the dechlorination of chloroaromatic compounds is potentially advantageous compared with traditional techniques such as adsorption on activated carbon or incineration. Recent studies have shown that the dechlorination of 4-CP (4-chlorophenol) by electrocatalytic hydrogenation on a palladized carbon cloth and of chlorophenoxy acetic acids on palladium-loaded carbon felt can be performed with good efficiencies. According to the literature, , the mechanism of the electrocatalytic hydrogenolysis of a carbon−halogen bond involves the steps described in eqs 1−4 …”
Section: Introductionmentioning
confidence: 99%
“…Because of its strong ability to intercalate hydrogen in its lattice, the palladium is the most common catalyst for ECH. It was shown to be much more effective in promoting the dechlorination reaction than platinum and Raney nickel. , Usually, a high degree of dispersity and the large surface areas of palladium are desirable for the ECH process. High surface areas of many conducting polymers favored their use as supporting materials for the development of new electrocatalysts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For chemical degradation of atrazine, many new techniques have been explored. These include photocatalytic degradation (Minero et al, 1996), advanced oxidation (Arántegui et al, 1995), Electrocatalytic dechlorination (Monson et al, 1998;Stock and Bunce, 2002), and reductive degradation by the use of zero-valent iron (Dombek et al, 2001), and Fenton reactions (Arnold et al, 1995). Chemical methods for atrazine breakdown was done with the help of Fenton's reagent (Larson et al, 1991).…”
Section: Atrazine Removal Technologiesmentioning
confidence: 99%
“…Various new techniques that have been proposed and explored for the destruction of chlorinated triazine herbicides, in particular atrazine included photocatalytic degradation [61], advanced oxidation [62][63][64][65], Fenton like reactions [66][67], electrocatalytic dechlorination [68] and reductive degradation by the use of zero-valent iron [69][70]. Chemical process using Fenton's reagent was tried to degrade atrazine.…”
Section: Chemical Degradationmentioning
confidence: 99%